Penerapan Model Problem Based Learnig (PBL) pada Materi Bangun Ruang Sisi Lengkung untuk Meningkatkan Hasil Belajar Siswa Kelas IX G SMP Negeri 2 Mataram - Purnamasari, Erni; Amrullah, Amrullah; Maksud, Maksud (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to improve the mathematics learning outcomes of ninth-grade students (Class IX G) at SMP Negeri 2 Mataram in the 2023/2024 academic year through the implementation of the Problem-Based Learning (PBL) model. The subjects of this study were 39 students from Class IX G. This research employed a Classroom Action Research (CAR) design, conducted over two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. Data were collected through learning outcome evaluation tests administered at the end of each cycle and analyzed using a quantitative descriptive approach. The results of the analysis showed an improvement in students’ learning outcomes on the topic of curved-surface solid geometry after the application of the PBL model. This improvement was evidenced by an increase in the percentage of students who achieved the minimum mastery criteria (KKM), from 76.51% in the first cycle with an average score of 76.51 to 87.18% in the second cycle with an average score of 83. These findings indicate that the implementation of Problem-Based Learning effectively enhances both the average learning outcomes and the proportion of students who meet the mastery criteria.